High interleukin-4 expression and interleukin-4 gene polymorphisms are associated with susceptibility to human paracoccidioidomycosis - Mendonca, Monica Sawan; Peracolli, Terezinha S. [UNESP]; Silva-Vergara, Mario Leon; Ribeiro, Silvio C.; Oliveira, Rafael Faria; Mendes, Rinaldo Poncio [UNESP]; Rodrigues, Virmondes (Fundaco Oswaldo Cruz, 2015)
Paracoccidioidomycosis (PCM) is caused by dimorphic fungi from the Paracoccidioides brasiliensis complex. Previous studies have demonstrated that the severity of disease is associated with a T-helper 2 immune response characterised by high interleukin (IL)-4 production. In the present study we analysed two polymorphisms in the IL-4 gene (-590 C/T and intron-3 microsatellite) in 76 patients with PCM and 73 control subjects from an endemic area. The production of IL-4 by peripheral blood mononuclear cells after antigen or phytohaemagglutinin stimulation was determined by ELISA. A significant correlation was observed between the RP2/RP2 intron-3 genotype and infection with Paracoccidioides sp. (p = 0.011), whereas the RP1/RP1 genotype was correlated with resistance. No significant correlation was observed for the IL-4 promoter polymorphism. Furthermore, the low IL-4 expression observed in the control group compared with patients was associated with the RP1/RP1 genotype. These results suggest that IL-4 polymorphisms might be associated with the ability of the host to control Paracoccidioides sp. infection. The relevance of this polymorphism is supported by the observation that patients with disease produce high levels of IL-4 following mitogen or antigen stimulation. The IL-4 gene is located in the cytokine cluster region of chromosome 5 where other polymorphisms have also been described.
Keywords: gene polymorphism; IL-4; Paracoccidioides brasiliensis; paracoccidioidomycosis